Developing an Online Test Battery for Testing EFL Pragmatic Competence: What Can It Tell Us? - Fadhlur Rahman; Ella Yuzar; Wanying Zhou (Pusat Studi Pendidikan Bahasa dan Sastra Inggris, 2023)
This study aims to develop a practical and reliable test to assess second language pragmatic knowledge as well as to investigate the effect of study abroad experience and proficiency level on EFL learners’ pragmatic competence. A total 59 participants, consisting of 34 females and 29 males, were categorized into groups based on their exposure to the target language and proficiency. The results show that the reliability of the test reaches ?=.798 which means it is acceptable for a language test. Further development of test items is required to achieve more adequate test reliability. The findings also suggest that learners' pragmatic knowledge can be influenced by both study-abroad experience and linguistic competence. These factors may contribute to learners' ability to appropriately respond to pragmatic utterances from the test. Thus, language learners should focus on increasing their linguistic proficiency to enhance their understanding and use of pragmatic language. This study underscores the importance of designing effective language pragmatic tests that incorporate a variety of pragmatics components and comprehensive instruments to achieve the desired test reliability and validity.